Pharmaceutical treatment of asthma symptoms in elite athletes - Doping or therapy - Elers, J.; Backer, V. (Allergic Diseases, 2012)
The frequency of asthma among the general population is around 7-10%; whereas the frequency of asthma among elite athletes is found to be higher, especially among endurance athletes (Pedersen et al 2008b). It seems as asthma is something they gain, as only one third of Olympic athletes had childhood asthma. Although asthma among the general public is a permanent phenomenon, it seems to be different in elite athletes, as asthma apparently disappeared after retiring from the sport (Fitch et al 2008).